Developing a hybrid visual perception game using the ADDIE approach for autism - Mohd Noor, Helmi Adly; Shahbodin, Faaizah; Che Pee @ Che Hanapi, Ahmad Naim; Yusof, Nur Fadiah; Yusoff, Mariana; Khoo, Linda Mei Sui; Jusoff, Kamaruzaman (American-Eurasian Network for Scientific Information, 2013)
Vision problems are frequently associated with autism. Currently, a systematic manual diagnosed has been developed to assess autism children. However, the method for diagnosed visual perception problem is still using manual and hands on technique. In this paper, a systematic research framework using analyze, design, develop, implement and evaluate (ADDIE) approach is proposed for a hybrid visual perception game to diagnose autism children. Thus, a technological solution to address visual perception problems among autism children can be done. It will benefit from intervention to improve perceptual skills among autism children. This serves as a guide and reference to build a prototype for further research. The outcome from this research and invention can be used for educational area and medical field.